High-strength steel sheet and method for producing same
By preparing upper bainite microstructure in steel plates and controlling dislocation density and crystal grain size, combined with specific heat treatment conditions, the problem of insufficient tensile strength and fatigue strength of steel plates in the prior art was solved, and a pulling of more than 980MPa was achieved Extension strength and excellent fatigue resistance, suitable for lightweight design of automotive parts.
Patent Information
- Application Number
- CN202380028202.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-24
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has failed to effectively improve the fatigue strength of the steel plate while increasing the tensile strength, especially in terms of tensile strength above 980 MPa and excellent fatigue resistance characteristics.
By preparing microstructures with the main phase of upper bainite and containing an appropriate amount of martensite and/or residual austenite phase, the dislocation density of the steel plate surface area is increased and the crystal grain size is controlled in combination with specific heat treatment and cooling conditions, high-strength hot-rolled steel plate with tensile strength or above and excellent fatigue strength was made.
The tensile strength of the steel plate above 980MPa and excellent fatigue resistance are achieved, ensuring the long life of the automotive parts and lightweight design, and significantly improving the automobile fuel efficiency.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength steel sheet (particularly a hot-rolled steel sheet) suitable as an automobile member, particularly having improved strength and fatigue resistance, and a method for producing the same. Background Art
[0002] In recent years, from the perspective of protecting the global environment, there has been a global demand for reducing CO2 emissions. In particular, there is a strong desire to improve the fuel efficiency of automobiles, and attention is paid to lightweighting of automobile bodies. Improving the strength of steel plates, which are raw materials for automobile components, and reducing the thickness of the steel plates are effective means for lightweighting without reducing the strength of the automobile body. In particular, steel plates with a tensile strength of 980 MPa or more are expected to be raw materials that can dramatically improve automobile fuel efficiency through thinning.
[0003] However, in order to ensure the durability that decreases with the thinning of automobile parts, it is necessary to improve the fatigue resistance of steel plates. Automobile parts, especially running parts such as suspension parts, are repeatedly loaded from tires. Therefore, if the fatigue strength is low, as the running distance increases, it may be lower than the durability of the parts assumed in the design. However, even if the strength of the steel plate is increased, the fatigue strength may not necessarily increase.
[0004] Various studies have been conducted so far to improve the fatigue strength of steel sheets while improving the tensile strength (Patent Documents 1 to 3).
[0005] Patent Document 1 discloses a technique related to a high-strength hot-rolled steel sheet having excellent formability and fatigue resistance by controlling the production conditions of hot rolling, making the main phase ferrite, and controlling the shape and dispersion form of inclusions.
[0006] Patent Document 2 discloses a technology for producing a high-strength hot-rolled steel sheet having excellent hole expandability and fatigue resistance by controlling the production conditions of hot rolling to make the main phase bainite with fine hard secondary phase dispersed therein and controlling the amount of solid solution Ti.
[0007] Patent Document 3 discloses a technology for producing a high-strength hot-rolled steel sheet having excellent formability, fracture characteristics, and fatigue resistance by using ferrite as the main phase and controlling the number density of cementite in ferrite grains and the size of the hard second phase and the number density of inclusions.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-31560
[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-012701
[0012] Patent Document 3: Japanese Patent Application No. 2021-505759 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, the conventional techniques described in Patent Documents 1 to 3 have the following problems.
[0015] The technology described in Patent Document 1 cannot obtain a tensile strength of 980 MPa or more.
[0016] The technology described in Patent Document 2 has not been fully studied regarding fatigue strength when actually used as an automobile part.
[0017] The technology described in Patent Document 3 provides a high-strength steel sheet having excellent fatigue resistance, but does not specify specific fatigue resistance.
[0018] As described above, conventionally, a technology for producing a high-strength hot-rolled steel sheet having a tensile strength of 980 MPa or more and excellent fatigue resistance has not yet been established.
[0019] Therefore, the present invention has been developed in view of the above circumstances, and an object of the present invention is to provide a high-strength hot-rolled steel sheet having a tensile strength of 980 MPa or more and excellent fatigue strength, and a method for producing the same.
[0020] Methods used to solve problems
[0021] In order to achieve the above-mentioned object, the inventors have conducted in-depth research to ensure a tensile strength of more than 980 MPa and improve the fatigue resistance of hot-rolled steel sheets. As a result, the following insights were discovered. That is, a microstructure in which the main phase is upper bainite and contains an appropriate amount of martensite and / or residual austenite phase as a hard second phase is made, so that the dislocation density of all phases in the surface region from the surface of the steel sheet to the position of 1 / 10 of the plate thickness is increased, and the grain size of all phases is controlled. As a result, a steel sheet with high strength of more than 980 MPa and excellent fatigue strength can be obtained after a heat treatment equivalent to coating baking.
[0022] It should be noted that the upper bainite phase mentioned here is an aggregate of lath ferrite with an orientation difference of less than 15°, and refers to a structure having Fe-based carbides and / or residual austenite phases between lath ferrites. However, this structure also includes a situation where there are no Fe-based carbides and / or residual austenite between lath ferrites.
[0023] Lath ferrite is different from laminar ferrite and polygonal ferrite in pearlite. Since lath ferrite has a lath shape and a high dislocation density inside, the two can be distinguished using SEM (scanning electron microscope) and TEM (transmission electron microscope).
[0024] In addition, when there is retained austenite between laths, only the lath-shaped ferrite portion is regarded as upper bainite and is distinguished from the retained austenite.
[0025] In addition, the contrast of the SEM image of the martensite and / or retained austenite phase is brighter than that of the upper bainite phase, the lower bainite phase, and the polygonal ferrite phase. Therefore, the martensite and / or retained austenite phase can be distinguished from these structures using SEM.
[0026] The martensite phase and the retained austenite phase have the same contrast in SEM, but can be distinguished from each other using the Electron Backscatter Diffraction Patterns (EBSD) method.
[0027] The dislocation density is measured by irradiating a steel material with X-rays and analyzing the intensity curve (line profile) of the obtained diffracted X-rays relative to the measurement angle or energy. The line profile analysis is performed in accordance with the "Evaluation method of dislocation density using X-ray diffraction" described in "Materials and Processes" Vol. 17 (2004) No. 3, P396-399. In the present invention, the dislocation density is calculated based on the half-value widths of (110), (211), and (220).
[0028] The present invention has been completed as a result of further studies based on the above findings, and the gist of the present invention is as follows.
[0029] [1] A high-strength steel sheet having a composition comprising, in mass%, 0.03-0.15% C, 0.1-3.0% Si, 0.8-3.0% Mn, 0.001-0.1%, 0.0001-0.03%, 0.001-2.0% Al, 0.001-0.01% N, and 0.0002-0.010% B, further comprising at least one selected from 0.01-0.30% Ti and 0.001-0.10% Nb, with the remainder being Fe and inevitable impurities, wherein in the microstructure, from the surface of the steel sheet to a position 1 / 10 of the sheet thickness, In the surface region of the steel sheet, an upper bainite phase with an area ratio of 75% or more and less than 98.5% is used as the main phase, a structure composed of a martensite phase and / or a retained austenite phase with an area ratio of 1.5% or more and less than 25% is used as the second phase, and a residual structure phase other than the upper bainite phase, the martensite phase and / or the retained austenite phase with an area ratio of 2.0% or less is included, the average grain size of all phases in the surface region from the steel sheet surface to the position of 1 / 10 of the plate thickness is 6.0 μm or less, and the dislocation density of all phases in the surface region from the steel sheet surface to the position of 1 / 10 of the plate thickness is 8.0×10 14 / m 2 above.
[0030] [2] The high-strength steel sheet according to [1], wherein the above-mentioned component composition further contains at least one group selected from the following groups a to c in terms of mass %, group a: at least one selected from Cu: 0.005-2.0%, Ni: 0.005-2.0%, Cr: 0.005-2.5%, V: 0.001-0.5% and Mo: 0.005-1.0%; group b: at least one selected from Sb: 0.005-0.2% and Sn: 0.001-0.05%; and group c: at least one selected from Ca: 0.0005-0.01%, Mg: 0.0005-0.01% and REM: 0.0005-0.01%.
[0031] [3] A method for producing a high-strength steel sheet, which is the method for producing a high-strength steel sheet according to [1] or [2], wherein a steel raw material having the above-mentioned composition is heated to a heating temperature of 1150°C or higher, the heated steel raw material is rough-rolled to produce a steel sheet, the steel sheet is finish-rolled under the conditions that a total reduction ratio in a temperature range of (RC1-150)°C or higher and a finish-rolling end temperature of (RC2-100)°C or higher and (RC2+50)°C or lower is 35% or higher, and the steel sheet after the finish rolling is The plate is cooled under the conditions that the time from the end of finish rolling to the start of cooling is within 2.0s, the average cooling rate based on the surface is 20°C / s or more, and the cooling stop temperature is Trs°C or more and (Trs+180)°C or less. The steel plate after the above cooling is coiled under the conditions that the coiling temperature is Trs°C or more and (Trs+180)°C or less, and is cooled to below (Trs-250)°C at an average cooling rate of less than 1°C / s, and is temper rolled under the conditions that the reduction rate is 0.1% or more and 5.0% or less.
[0032] Among them, RC1, RC2, and Trs are defined by the following equations (1), (2), and (3), respectively.
[0033] RC1(℃)=900+120×C+100×N+10×Mn+500×Ti+5000×B+10×Cr+50×Mo+1500×Nb+150×V…(1)
[0034] RC2(℃)=750+120×C+100×N+10×Mn+250×Ti+5000×B+10×Cr+50×Mo+750×Nb+150×V…(2)
[0035] Trs(℃)=500-450×C-35×Mn-15×Cr-10×Ni-20×Mo…(3)
[0036] Here, the symbol of each element in the above formulas (1), (2), and (3) represents the content (mass %) of each element, and when the element is not contained, it is set to 0.
[0037] Effects of the Invention
[0038] According to the present invention, a high-strength steel sheet having a tensile strength of 980 MPa or more and excellent fatigue resistance and a method for producing the same can be provided.
[0039] When the high-strength steel sheet of the present invention is applied to automobile running parts such as suspensions, structural parts, skeleton parts, and truck frame parts, safety can be ensured and the weight of the automobile body can be reduced, thus exerting a significant effect industrially.
[0040] It should be noted that, in the present invention, excellent fatigue resistance means that in the complete alternating plane bending fatigue test, 2×10 6 The ratio of the plane bending fatigue strength to the tensile strength (fatigue limit ratio) is 0.50 or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram showing the shape of a test piece for a plane bending fatigue test in the present invention. DETAILED DESCRIPTION
[0042] Hereinafter, embodiments of the present invention will be described. It should be noted that the following description shows examples of common embodiments of the present invention, and the present invention is not limited to the following embodiments.
[0043] The steel sheet has the following chemical composition. In the following description, "%" as a unit of the content of an element in the chemical composition means "mass %" unless otherwise specified.
[0044] <C:0.03~0.15%>
[0045] C promotes the formation of bainite by improving hardenability, and is an element effective for improving strength. When the C content is less than 0.03%, such an effect cannot be fully obtained, and a tensile strength of more than 980MPa cannot be obtained. Therefore, the C content is more than 0.03%, preferably more than 0.04%, and more preferably more than 0.05%. On the other hand, when the C content exceeds 0.15%, martensite and retained austenite increase, and sufficient fatigue resistance cannot be obtained. Therefore, the C content is less than 0.15%, preferably less than 0.14%, and more preferably less than 0.13%.
[0046] <Si: 0.1~3.0%>
[0047] Si strengthens the steel by solid solution, and contributes to the improvement of the strength of the steel. Therefore, the Si content is 0.1% or more, preferably 0.3% or more, and more preferably 0.5% or more. On the other hand, Si is an element that promotes the formation of ferrite. When the Si content exceeds 3.0%, ferrite is formed, and the fatigue resistance is reduced. Therefore, the Si content is 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less.
[0048] <Mn: 0.8~3.0%>
[0049] Mn is an element that stabilizes austenite, and is an element that is effective for suppressing the formation of ferrite and improving strength. When the Mn content is less than 0.8%, such an effect cannot be fully obtained, and ferrite, etc. are generated, and a tensile strength of more than 980MPa cannot be obtained. Therefore, the Mn content is more than 0.8%, preferably more than 1.0%, and more preferably more than 1.2%. On the other hand, when the Mn content exceeds 3.0%, martensite and retained austenite increase, and sufficient fatigue resistance characteristics cannot be obtained. Therefore, the Mn content is less than 3.0%, preferably less than 2.8%, and more preferably less than 2.5%.
[0050] <P: 0.001~0.1%>
[0051] P deteriorates weldability, so its amount is preferably reduced as much as possible. In the present invention, the P content can be allowed to be up to 0.1%. Therefore, the P content is set to 0.1% or less. When the P content is less than 0.001%, it leads to a decrease in production efficiency, so the lower limit is set to 0.001% or more.
[0052] <S:0.0001~0.03%>
[0053] S deteriorates weldability, so its amount is preferably reduced as much as possible. In the present invention, the S content can be allowed to be up to 0.03%. Therefore, the S content is set to 0.03% or less. When the content is less than 0.0001%, it leads to a decrease in production efficiency, so the lower limit is set to 0.0001% or more.
[0054] <Al: 0.001~2.0%>
[0055] Al acts as a deoxidizer and is an effective element for improving the cleanliness of steel. When Al is too little, its effect may not be sufficient. Therefore, the Al content is 0.001% or more, preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, Al is an element that promotes the formation of ferrite. When the Al content exceeds 2.0%, ferrite is generated, which reduces fatigue strength. Therefore, the Al content is 2.0% or less, preferably 1.8% or less, and more preferably 1.6% or less.
[0056] <N: 0.001~0.01%>
[0057] N combines with elements that form nitrides to precipitate in the form of nitrides, which contributes to the refinement of crystal grains. In order to obtain this effect, it needs to be 0.001% or more. However, N easily combines with Ti at high temperatures to form coarse nitrides, and excessive inclusion reduces fatigue resistance. Therefore, the N content is 0.01% or less, preferably 0.008% or less, and more preferably 0.006% or less.
[0058] <B:0.0002~0.010%>
[0059] B segregates at the original austenite grain boundary, inhibits the formation of ferrite, thereby promoting the formation of upper bainite, and is an effective element for improving the strength of the steel plate. In order to show these effects, it is necessary to set the B content to 0.0002% or more. Therefore, the B content is set to 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0007% or more. On the other hand, when the B content exceeds 0.010%, the above effect is saturated. Therefore, the B content is set to 0.010% or less, preferably 0.009% or less, and more preferably 0.008% or less.
[0060] <Ti: 0.01 to 0.30%, Nb: 0.001 to 0.10% or more>
[0061] Ti and Nb form carbides, which are elements effective for improving strength through precipitation strengthening. Therefore, it is necessary to contain at least one of Ti and Nb. The lower limit of the content is set to Ti: 0.01% or more, Nb: 0.001% or more, preferably Ti: 0.02% or more, Nb: 0.002% or more, more preferably Ti: 0.03% or more, Nb: 0.003% or more. On the other hand, when the Ti and Nb contents exceed Ti: 0.30% and Nb: 0.10% respectively, sometimes the carbides are coarsened and the hardenability is reduced, and the steel structure of the present invention cannot be obtained. Therefore, the upper limits of the Ti and Nb contents are set to Ti: 0.30% or less, Nb: 0.10% or less, preferably Ti: 0.25% or less, Nb: 0.08% or less, more preferably Ti: 0.20% or less, Nb: 0.05% or less.
[0062] The balance is Fe and inevitable impurities.
[0063] The above components are the basic component composition of the high-strength steel sheet of the present invention, and the following elements may be contained as necessary.
[0064] Cr, Ni, Cu, V, and Mo are elements that stabilize austenite and are effective elements for inhibiting the formation of ferrite and improving strength. In order to obtain such an effect, it is preferred to contain one or more of them. In the case of containing one or more of Cr, Ni, Cu, V, and Mo, it is preferred to set the respective contents to Cu: 0.005-2.0%, Ni: 0.005-2.0%, Cr: 0.005-2.5%, V: 0.001-0.5%, and Mo: 0.005-1.0%. When the contents of Cr, Ni, Cu, V, and Mo exceed the above upper limits, it is sometimes easy to retain martensite and residual austenite and the steel structure of the present invention cannot be obtained. The lower limit of the Cr content is more preferably set to 0.1% or more. The upper limit of the more preferred Cu content is set to 0.6% or less. The lower limit of the Ni content is more preferably set to 0.1% or more. The upper limit of the more preferred Ni content is set to 0.6% or less. The lower limit of the Cu content is more preferably set to 0.1% or more. The upper limit of the Cu content is more preferably set to 0.6% or less. The lower limit of the V content is more preferably set to 0.005% or more. The upper limit of the V content is more preferably set to 0.3% or less. The lower limit of the Mo content is more preferably set to 0.1% or more. The upper limit of the Mo content is more preferably set to 0.5% or less.
[0065] Sb inhibits the detachment of elements from the surface of the steel material when the steel material is heated, and is an element effective in inhibiting the reduction in the strength of the steel. Therefore, when Sb is contained, the content is preferably set to 0.005-0.2%. When the Sb content exceeds the above upper limit, it sometimes causes embrittlement of the steel plate. The lower limit of the Sb content is more preferably set to 0.01% or more. The more preferred upper limit of the Sb content is set to 0.050% or less.
[0066] Sn inhibits the formation of pearlite and is an effective element for inhibiting the reduction of steel strength. In order to obtain such an effect, when Sn is contained, the content is preferably set to 0.001-0.05%. When the Sn content exceeds the above upper limit, it sometimes causes embrittlement of the steel sheet. The lower limit of the Sn content is more preferably set to 0.005% or more. The more preferred upper limit of the Sn content is set to 0.03% or less.
[0067] Ca, Mg, and REM are elements that are effective in improving workability by controlling the morphology of inclusions. In order to obtain such an effect, it is preferred to contain one or more of them. In the case of containing one or more of Ca, Mg, and REM, it is preferred to set the respective contents to Ca: 0.0005-0.01%, Mg: 0.0005-0.01%, and REM: 0.0005-0.01%. On the other hand, when the contents of Ca, Mg, and REM exceed the above upper limits, the amount of inclusions sometimes increases and workability deteriorates. The lower limit of the Ca content is more preferably set to 0.001% or more. The upper limit of the more preferred Ca content is set to 0.005% or less. The lower limit of the Mg content is more preferably set to 0.001% or more. The upper limit of the more preferred Mg content is set to 0.005% or less. The lower limit of the REM content is more preferably set to 0.001% or more. The upper limit of the more preferred REM content is set to 0.005% or less. It should be noted that REM (rare earth elements) is a general term for 15 elements including Sc, Y, and lanthanum (La) with an atomic number of 57 to lutetium (Lu) with an atomic number of 71, and the REM content mentioned here is the total content of these elements.
[0068] It should be noted that even if the contents of Mo, V, Cr, Ni, Cu, Sb, Sn, Ca, Mg, and REM are less than the above lower limits, the effects of the present invention are not impaired. Therefore, when the contents of these components are less than the above lower limits, these elements are included as unavoidable impurities.
[0069] Next, the microstructure of the high-strength steel sheet of the present invention will be described.
[0070] The high-strength steel sheet of the present invention has the following microstructure in the surface region from the surface of the steel sheet to the position of 1 / 10 of the sheet thickness. That is, the upper bainite phase with an area ratio of 75% or more and less than 98.5% is used as the main phase. In addition, the structure composed of the martensite phase and / or the residual austenite phase with an area ratio of 1.5% or more and less than 25% is used as the second phase. The average grain size of all phases in the above-mentioned surface region is less than 6.0 μm, and the dislocation density of all phases is 8.0×10 14 / m 2 above.
[0071] <Upper bainite phase: 75% or more and less than 98.5% by area ratio>
[0072] The microstructure of the high-strength steel sheet of the present invention includes upper bainite as a main phase. When the area ratio of the upper bainite is less than 75%, excellent fatigue strength cannot be obtained. Therefore, the lower limit of the area ratio of the upper bainite is set to 75% or more, preferably 85% or more. On the other hand, when the upper bainite phase is 98.5% or more, the desired dislocation density cannot be obtained. Therefore, the upper limit of the area ratio of the upper bainite is set to less than 98.5%, preferably 97% or less.
[0073] <Martensite phase and / or retained austenite phase: 1.5% or more and less than 25% by area ratio>
[0074] The microstructure of the high-strength steel plate of the present invention includes a martensite phase and / or a retained austenite phase. When the martensite phase and / or the retained austenite phase is less than 1.5%, a tensile strength of more than 980MPa and excellent fatigue resistance cannot be achieved. On the other hand, when the area ratio of martensite and / or retained austenite is more than 25%, the interface between martensite and / or retained austenite and upper bainite, which may become the starting point of fatigue crack generation, increases, and fatigue resistance decreases. For this reason, it is necessary to set the total area ratio of martensite and / or retained austenite to less than 25%. It is preferably set to less than 20%, and more preferably set to less than 15%. It should be noted that the martensite of the present invention refers to martensite in a quenched state.
[0075] The effect of the present invention is not impaired when the residual microstructure phase other than the upper bainite, martensite and / or retained austenite is 2.0% or less in terms of area ratio at most. The residual microstructure includes, for example, well-known microstructures such as ferrite and pearlite.
[0076] <Average grain size 6.0 μm or less>
[0077] It can be said that the generation of fatigue cracks is caused by the slip deformation within the grains of the surface layer. The grain boundaries make it difficult for the slip deformation to propagate to the adjacent grains, and as a result, the generation of cracks can be delayed. That is, the fatigue strength can be improved by grain refinement. In addition, the improvement of strength is also contributed to by refining the grain size. Therefore, the average grain size is less than 6.0 μm, preferably less than 5.0 μm. On the other hand, if the average grain size is too small, the strength may increase and the elongation may decrease. Therefore, the average grain size is preferably set to more than 2.0 μm. It should be noted that the average grain size described here refers to the average grain size of all phases in the surface region from the surface of the steel plate to the position of 1 / 10 of the plate thickness. In addition, in the case where the surface region until the position of 1 / 10 of the plate thickness contains a residual tissue phase, the residual tissue phase is also included in the above-mentioned "all phases".
[0078] <Dislocation density is 8.0×10 14 / m 2Above>
[0079] Most fatigue cracks originate from the surface of the steel plate and enter the fatigue crack propagation stage after growing to a length of tens of μm. In high cycle fatigue, the number of repetitions until cracks occur accounts for most of the fatigue life. Therefore, in order to improve the 2×10 6 In order to achieve the fatigue strength of the steel plate, it is necessary to suppress the generation of cracks. It is important to control the dislocation behavior in the surface area from the surface of the steel plate to the position of 1 / 10 of the plate thickness. In the high-strength steel plate of the present invention, the dislocation introduced into the structure is pinned due to the heat treatment in the subsequent process, which becomes an obstacle to the movement of dislocations. Thus, the movement and rearrangement of dislocations are prevented, the repeated softening is delayed, and the fatigue resistance is improved. In order to achieve this effect, the dislocation density is set to 8.0×10 14 / m 2 More than 1.0×10 15 / m 2 More preferably, 1.2×10 15 / m 2 The upper limit of dislocation density is not particularly limited, but is preferably 4.0×10 15 / m 2 Below. It should be noted that it is most important to control the dislocation density of the main phase in the surface region from the surface of the steel plate to the position of 1 / 10 of the plate thickness. However, since it is difficult to measure only the dislocation density of the main phase, the dislocation density of the present invention refers to the dislocation density of all phases in the surface region up to the position of 1 / 10 of the plate thickness. It should be noted that when the surface region up to the position of 1 / 10 of the plate thickness contains a residual microstructure phase, the residual microstructure phase is also included in the above-mentioned "all phases".
[0080] The high-strength steel sheet of the present invention has a tensile strength of 980 MPa or more and a fatigue limit ratio of 0.50 or more. Here, the fatigue limit ratio refers to 2×10 6 Therefore, the high-strength steel sheet of the present invention can ensure safety even when the tensile strength is high and the wall thickness is thin, and can be applied to components of trucks and passenger cars.
[0081] In addition, in the present invention, the area ratios and mechanical properties of the above-mentioned respective structures are values measured by the methods described in the Examples.
[0082] Next, a method for producing a high-strength steel sheet according to an embodiment of the present invention will be described. In the following description, unless otherwise specified, "°C" for temperature refers to the surface temperature of an object (steel material or steel sheet).
[0083] The high-strength steel sheet of the present invention can be produced by sequentially subjecting a steel material to the following treatments (1) to (6). Each step will be described below.
[0084] (1) Heating
[0085] (2) Hot rolling
[0086] (3) Cooling (first cooling)
[0087] (4) Coiling
[0088] (5) Cooling (second cooling)
[0089] (6) Temper rolling
[0090] It should be noted that, as a steel raw material, any steel raw material can be used as long as it has the above-mentioned composition. The composition of the high-strength steel plate finally obtained is the same as the composition of the steel raw material used. As a steel raw material, for example, a steel billet can be used. In addition, the manufacturing method of the steel raw material is not particularly limited. For example, molten steel having the above-mentioned composition can be smelted by a known method such as a converter, and the steel raw material can be obtained by a casting method such as continuous casting. Methods other than continuous casting such as ingot casting-blowing rolling method can also be used. In addition, scrap iron can also be used as a raw material. After being manufactured by a method such as a continuous casting method, the steel raw material can be directly supplied to the next heating process. In addition, the steel raw material that becomes a warm sheet or a cold sheet after cooling can also be supplied to the heating process.
[0091] (1) Heating
[0092] First, the steel material is heated to a heating temperature of 1150°C or higher. In the steel material after cooling to a low temperature, most of the carbonitride-forming elements such as Ti exist unevenly in the form of coarse carbonitrides. The presence of this coarse and uneven precipitate usually leads to the deterioration of various properties (for example, strength, fatigue resistance, etc.) required for high-strength steel plates for truck and passenger car parts. Therefore, it is necessary to heat the steel material before hot rolling to dissolve the coarse precipitates. Therefore, the heating temperature of the steel material is above 1150°C, preferably above 1180°C, and more preferably above 1200°C. On the other hand, when the heating temperature of the steel material becomes too high, the yield is reduced due to the generation of steel billet defects and scale peeling. Therefore, the heating temperature of the steel material is preferably below 1350°C, more preferably below 1300°C, and further preferably below 1280°C.
[0093] During heating, from the viewpoint of making the temperature of the steel raw material uniform, it is preferred to heat the steel raw material to the above-mentioned heating temperature and then maintain it at the heating temperature. The time (holding time) maintained at the heating temperature is not particularly limited, and from the viewpoint of improving the uniformity of the temperature of the steel raw material, it is preferably set to 1800 seconds or more. On the other hand, when the holding time exceeds 10000 seconds, the amount of oxide scale generated sometimes increases. As a result, oxide scale embedding and the like are sometimes likely to occur in the subsequent hot rolling, resulting in a reduction in the yield rate due to poor surface defects. Therefore, the holding time is preferably set to 10000 seconds or less, and more preferably set to 8000 seconds or less. It should be noted that the steel raw material before hot rolling can be directly supplied to hot rolling (direct rolling) in a high temperature state after casting (that is, in a state where the temperature in the range of the above-mentioned heating temperature is maintained).
[0094] (2) Hot rolling
[0095] Next, the heated (or cast high temperature) steel raw material is subjected to hot rolling including rough rolling and finish rolling. For the rough rolling, the conditions are not particularly limited as long as the desired thin slab size can be ensured. The steel raw material is subjected to rough rolling to obtain a rough rolled plate. The obtained rough rolled plate can be descaled by spraying high pressure water at the inlet side of the finishing mill before the finish rolling (high pressure water descaling).
[0096] Next, in the present invention, in the finish rolling, when the temperature RC1 and the temperature RC2 are defined by the following formulas (1) and (2), the total reduction rate in the temperature range of (RC1-150)°C and RC1°C is set to 35% or more. The residence time in this temperature range is not particularly specified and can be 3 seconds or more and 20 seconds or less. In addition, the finish rolling end temperature is set to (RC2-100)°C or more and (RC2+50)°C or less. RC1 is the austenite 50% recrystallization temperature estimated from the component composition, and RC2 is the austenite recrystallization lower limit temperature estimated from the component composition. When the total reduction rate in the temperature range of (RC1-150)°C and RC1°C is less than 35%, the average grain size becomes larger and the fatigue resistance improvement effect cannot be obtained. Therefore, the total reduction rate in the temperature range of (RC1-150)°C and RC1°C is 35% or more, preferably 45% or more, and more preferably 60% or more.
[0097] In addition, hot rolling is performed under the condition that the finishing temperature of the finishing rolling is above (RC2-100)°C and below (RC2+50)°C. When the finishing temperature of the finishing rolling is lower than (RC2-100)°C, ferrite is generated and a tensile strength of 980MPa or more cannot be obtained. Therefore, the finishing temperature of the finishing rolling is above (RC2-100)°C, preferably above (RC2-90)°C, and more preferably above (RC2-70)°C. On the other hand, when the finishing temperature of the finishing rolling is higher than (RC2+50)°C, the austenite grains coarsen and the average grain size of the upper bainite increases, so the strength decreases. Therefore, the finishing temperature of the finishing rolling is below (RC2+50)°C, preferably below (RC2+40)°C, and more preferably below (RC2+30)°C. It should be noted that RC1 and RC2 are defined by the following formulas (1) and (2).
[0098] RC1(℃)=900+120×C+100×N+10×Mn+500×Ti+5000×B+10×Cr+50×Mo+1500×Nb+150×V…(1)
[0099] RC2(℃)=750+120×C+100×N+10×Mn+250×Ti+5000×B+10×Cr+50×Mo+750×Nb+150×V…(2)
[0100] Here, the symbol of each element in the above formula (1) and (2) represents the content (mass %) of each element, and when the element is not contained, it is set to 0.
[0101] (3) Cooling (first cooling)
[0102] Next, the obtained hot-rolled steel sheet is cooled (first cooling). At this time, the time from the end of hot rolling to the start of cooling (cooling start time) is set to within 2.0 seconds after the end of finish rolling. When the cooling start time exceeds 2.0 seconds, grain growth of austenite grains occurs, and a tensile strength of more than 980 MPa cannot be ensured. Therefore, the cooling start time is within 2.0 seconds, preferably within 1.5 seconds, and more preferably within 1.0 seconds.
[0103] During cooling, when the average cooling rate from the finishing temperature to the cooling stop temperature is too slow, ferrite transformation occurs before the upper bainite transformation, and the upper bainite phase with the desired area ratio cannot be obtained. Therefore, the average cooling rate is above 20°C / s, preferably above 30°C / s, and more preferably above 50°C / s. On the other hand, the upper limit is not particularly limited. When it is too fast, it is difficult to manage the cooling stop temperature, and it is sometimes difficult to obtain the desired microstructure. Therefore, it is preferably below 500°C / s, more preferably below 300°C / s, and further preferably below 150°C / s. In addition, during cooling, forced cooling can be performed in a manner that achieves the above-mentioned average cooling rate. The cooling method is not particularly limited, and for example, it is preferably carried out by water cooling.
[0104] The cooling stop temperature is set to be above Trs°C and below (Trs+180)°C. When the cooling stop temperature is lower than Trs°C, the microstructure becomes lower bainite. Lower bainite is a high-strength structure, but the fatigue resistance after heat treatment is low. Therefore, the cooling stop temperature is set to be above Trs°C. On the other hand, when the cooling stop temperature is higher than (Trs+180)°C, ferrite is generated, so a tensile strength of more than 980 MPa cannot be obtained. Therefore, the cooling stop temperature is set to be below (Trs+180)°C. It should be noted that Trs is defined by the following formula (3).
[0105] Trs(℃)=500-450×C-35×Mn-15×Cr-10×Ni-20×Mo…(3)
[0106] Here, each element symbol in the above formula (3) represents the content (mass %) of each element, and when not contained, it is set to 0.
[0107] (4) Coiling
[0108] Next, the cooled hot-rolled steel sheet is coiled under the condition that the coiling temperature is Trs°C or higher and (Trs+180)°C or lower. When the coiling temperature is lower than Trs°C, the lower bainite transformation proceeds after coiling, and the desired martensite and / or retained austenite cannot be obtained. Therefore, the coiling temperature is higher than Trs°C, preferably higher than (Trs+10)°C, and more preferably higher than (Trs+30)°C. On the other hand, when the coiling temperature is higher than (Trs+180)°C, ferrite is generated, so a tensile strength of 980MPa or more cannot be obtained. Therefore, the coiling temperature is lower than (Trs+180)°C, preferably lower than (Trs+150)°C, and more preferably lower than (Trs+120)°C.
[0109] (5) Cooling (second cooling)
[0110] Next, cool to below (Trs-250)°C at an average cooling rate of less than 1°C / s (second cooling). When the average cooling rate from the coiling temperature to below (Trs-250°C) exceeds 1°C / s, the bainite transformation is not sufficient, the martensite and retained austenite increase, and the microstructure of the present invention cannot be obtained. Therefore, the average cooling rate from the coiling temperature to below (Trs-250)°C is less than 1°C / s, preferably less than 0.8°C / s, and more preferably less than 0.5°C / s. Cooling can be performed to any temperature below (Trs-250°C), preferably to about 10°C to about 30°C. It should be noted that cooling can be performed in any form, for example, it can be performed in the state of the coil after coiling.
[0111] (6) Temper rolling
[0112] Next, the steel sheet after cooling is subjected to temper rolling under the condition of a reduction ratio of 0.1% or more and 5.0% or less. When the reduction ratio is less than 0.1%, the dislocation density is insufficient and excellent fatigue strength cannot be obtained. Therefore, the reduction ratio is 0.1% or more, preferably 0.3% or more, and more preferably 0.5% or more. On the other hand, temper rolling exceeding 5.0% increases the load on the roll and increases the number of replacements, thereby increasing the manufacturing cost. Therefore, the reduction ratio is 5.0% or less, preferably 4.0% or less, and more preferably 3.0% or less.
[0113] The high-strength steel sheet of the present invention can be manufactured through the above steps. It should be noted that after temper rolling, the oxide scale formed on the surface can be removed by a conventional method, such as pickling.
[0114] Example
[0115] Molten steel having the composition shown in Table 1 was melted in a converter, and billets as steel raw materials were produced by a continuous casting method.
[0116]
[0117] The obtained steel material was heated to the heating temperature shown in Table 2, and then the heated steel material was subjected to hot rolling including rough rolling and finish rolling to obtain a hot rolled steel sheet. Table 2 shows the finish rolling end temperature in the hot rolling.
[0118] Next, the obtained hot-rolled steel plate is cooled under the conditions of the average cooling rate and cooling stop temperature shown in Table 2 (first cooling). The cooled hot-rolled steel plate is coiled at the coiling temperature shown in Table 2, and the coiled steel plate is cooled at the average cooling rate shown in Table 2 (second cooling) to obtain a high-strength steel plate. After cooling, temper rolling is performed at the reduction rate shown in Table 2, and pickling is performed. For pickling, a hydrochloric acid aqueous solution with a concentration of 10% by mass is used at a temperature of 85°C. Next, the steel plate is subjected to a heat treatment equivalent to a coating baking treatment (170°C, 20 minutes) to produce a high-strength hot-rolled steel plate.
[0119]
[0120] Test pieces were cut out from the obtained high-strength steel sheets, and the microstructure and mechanical properties were evaluated by the procedures described below.
[0121] <Microstructure>
[0122] A test piece for microstructure observation was cut from the obtained high-strength steel plate in the manner of observing the plate thickness section parallel to the rolling direction. The surface of the obtained test piece was polished, and then the surface was corroded using a corrosive solution (3% nitric acid ethanol solution), thereby making the microstructure visible. Next, for the surface layer from the surface to the position of 1 / 10 of the plate thickness, 10 fields of view were photographed at a magnification of 5000 times using a scanning electron microscope (SEM) to obtain a SEM image of the microstructure. The obtained SEM image was analyzed by image processing, and the area ratios of upper bainite (UB), polygonal ferrite (F), and lower bainite (LB) were quantified. In addition, martensite (M) and retained austenite (γ) were difficult to distinguish using SEM. Therefore, the electron backscatter diffraction (EBSD) method was used for identification, and the area ratios and average grain sizes of each microstructure were obtained. The area ratios and average grain sizes of each measured microstructure are shown in Table 3. In addition, Table 3 also shows the total area ratio (M+γ) of martensite and retained austenite.
[0123] <Tensile test>
[0124] From the obtained hot-rolled steel sheet, a JIS No. 5 tensile test piece (JIS Z 2201) was cut so that the tensile direction was perpendicular to the rolling direction, and a strain rate of 10 -3 / s was subjected to a tensile test in accordance with the provisions of JIS Z 2241 to determine the tensile strength. In the present invention, a tensile strength of 980 MPa or more was considered acceptable. The results are shown in Table 3.
[0125] <Plane bending fatigue test>
[0126] The obtained hot-rolled steel sheets were cut into pieces so that the length direction of the test piece was perpendicular to the rolling direction. Figure 1 The test piece with the dimensions and shape shown in the figure was subjected to a plane bending fatigue test in accordance with the provisions of JIS Z 2275. The stress loading mode was as follows: the stress ratio was set to R = -1 and the frequency was set to f = 25 Hz. The load stress amplitude was changed in 6 stages, and the stress cycle until fracture was measured to obtain the SN curve and the 2×10 6 In the present invention, when the value of the fatigue limit ratio obtained by dividing the fatigue limit by the tensile strength obtained by the tensile test is 0.50 or more, it is evaluated as excellent fatigue resistance. The results are shown in Table 3.
[0127]
[0128] The inventive examples are all high-strength steel sheets having a tensile strength of 980 MPa or more and excellent fatigue resistance. On the other hand, the comparative examples outside the scope of the present invention did not obtain a tensile strength of 980 MPa or more or excellent fatigue resistance.
Claims
1. A high-strength steel sheet having a composition comprising, in mass%, 0.03-0.15% C, 0.1-3.0% Si, 0.8-3.0% Mn, 0.001-0.1%, 0.0001-0.03%, 0.001-2.0% Al, 0.001-0.01% N, and 0.0002-0.010% B, further comprising at least one selected from 0.01-0.30% Ti and 0.001-0.10% Nb, with the remainder being Fe and unavoidable impurities, In the microstructure, in the surface region from the steel plate surface to the position of 1 / 10 of the plate thickness, the upper bainite phase is used as the main phase with an area ratio of 75% or more and less than 98.5%. The second phase is a structure composed of a martensite phase and / or a retained austenite phase with an area ratio of 1.5% or more and less than 25%. The residual microstructure phase other than the upper bainite phase, the martensite phase and / or the retained austenite phase has an area ratio of 2.0% or less, The average grain size of all phases in the surface layer region from the steel plate surface to the position of 1 / 10 of the plate thickness is 6.0 μm or less. The dislocation density of all phases in the surface region from the steel plate surface to the position of 1 / 10 of the plate thickness is 8.0×10 14 / m 2 above.
2. The high-strength steel plate according to claim 1, wherein: The above-mentioned component composition further contains, in terms of mass %, at least one selected from the following groups a to c: Group a: at least one selected from Cu: 0.005-2.0%, Ni: 0.005-2.0%, Cr: 0.005-2.5%, V: 0.001-0.5% and Mo: 0.005-1.0%; Group b: at least one selected from Sb: 0.005-0.2%, Sn: 0.001-0.05%; and Group c: at least one selected from Ca: 0.0005-0.01%, Mg: 0.0005-0.01% and REM: 0.0005-0.01%.
3. A method for producing a high-strength steel sheet, which is the method for producing a high-strength steel sheet according to claim 1 or 2, wherein: The steel material having the above composition is heated to a heating temperature of 1150° C. or higher. The heated steel material is roughly rolled to produce steel plates. The steel sheet is finish rolled at a total reduction ratio of 35% or more in a temperature range of (RC1-150)°C to RC1°C and a finish rolling end temperature of (RC2-100)°C to (RC2+50)°C. The steel sheet after finish rolling is cooled under the conditions that the time from the end of finish rolling to the start of cooling is within 2.0 seconds, the average cooling rate on the surface is 20°C / s or more, and the cooling stop temperature is Trs°C or more and (Trs+180)°C or less, The cooled steel sheet is coiled at a coiling temperature of Trs°C or higher and (Trs+180)°C or lower. Cool to below (Trs-250)°C at an average cooling rate of less than 1°C / s, Temper rolling is performed under the condition of a reduction ratio of 0.1% or more and 5.0% or less. Where RC1, RC2, and Trs are defined by the following equations (1), (2), and (3), respectively: RC1(℃)=900+120×C+100×N+10×Mn+500×Ti+5000×B+10×Cr+50×Mo+1500×Nb+150×V…(1) RC2(℃)=750+120×C+100×N+10×Mn+250×Ti+5000×B+10×Cr+50×Mo+750×Nb+150×V…(2) Trs(℃)=500-450×C-35×Mn-15×Cr-10×Ni-20×Mo…(3) Here, the symbol of each element in the above formula (1), (2), and (3) represents the content (mass %) of each element, and when the element is not contained, it is set to 0.
Citation Information
Patent Citations
High-strength hot-rolled steel plate exhibiting superior stretch flange workability and fatigue resistance properties, and method of manufacturing the same
JP2012012701A
Hot rolled steel sheet excellent in moldability, fracture characteristic and fatigue characteristic, and method for producing the same
JP2014031560A
High strength hot rolled steel and method for manufacturing high strength hot rolled steel
JP2021505759A
Cited By
Corrosion-fatigue-resistant ultrahigh-strength marine steel and preparation method thereof
CN121575326A